Resilient forests for the future - Annika Perry; Filippos A. Aravanopoulos; Katharina Birgit Budde; Ole Kim Hansen; Christian Rellstab; Hilke Schroeder; Alexandru Lucian Curtu (Tree Genetics & Genomes, 2024)
Forest ecosystems are of global importance, ecologically, economically and culturally. However, despite their fundamental role in mitigating the worst effects of climate change, to date there have been surprisingly few resources devoted to defining, conserving and planning resilient forests for the future. Progress in this field of research, which requires international and interdisciplinary cooperation, collaboration and communication, was presented and discussed at the second biannual conference of the European Research Group, Evoltree ( https://www.evoltree.eu ). Over four days more than 140 scientists met to share developments and to discuss forest ecology, genetics, genomics and evolution with a focus on realising “Resilient Forests for the Future”. From examining evolutionary dynamics and using the past to understand future responses, to evaluating breeding approaches and the sustainable use of forest genetic resources, the conference addressed critical themes with relevance to this topic. The role of genomics in conservation, investigation of biotic interactions and identifying climate resilient forests were also explored. Finally, innovative methods and approaches which promise to increase the scale and speed with which forest evolutionary research can progress were introduced and evaluated. The Evoltree network and conference series provides invaluable opportunities to share knowledge and increase collaboration on forest genetic research, the need for which has never been greater or more urgent.